New systematic data on females of the genus Dolichopus Latreille, 1796 (Diptera: Dolichopodidae) - I.I. Kornev; O.P. Negrobov; O.O. Maslova (Кавказский энтомологический бюллетень, 2011)
The descriptions of unknown females of species Dolichopus jacutensis Stackelberg, 1929, Dolichopus amurensis Stackelberg, 1930 and Dolichopus angustipennis Kertesz, 1901 are given. The females of species Dolichopus amurensis and Dolichopus bisetulatus Negrobov, 1977 are inserted into the key of Palaearctic region for the first time.